Restorative Justice Bagi Anak Pelaku Pidana Dalam KUHP Baru di Indonesia - Irawan, Andrie; Wahyono, Wahyono (Eastasouth Institute, 2024)
The aim of this research is to determine the application of restorative justice to children who are criminals in the juvenile criminal justice system in Indonesia and to reveal the problems of obstacles in the application of restorative justice as an alternative in the process of implementing the justice system for children in conflict with the law. This research methodology is included in the category of normative legal research, because normative research mainly uses library materials as a source of research data or also known as (library research), a method used to collect data from various literature. This research is descriptive analysis, which is included in the scope of research that describes, examines, explains precisely and analyzes the laws and regulations related to this research. The results of the research can be concluded that, First, the existence of Law Number 1 of 2023 concerning the Criminal Code (UU KUHP) as the new Criminal Code (KUHP) in Indonesia seeks to implement the legal ideals of restorative justice. the only concepts that are substantively built into the newly passed Criminal Code.